Governance of the territorial entrepreneurial discovery process: looking under the bonnet of RIS3 - Aranguren, Mari José; Magro, Edurne; Navarro, Mikel; Wilson, James R. (Regional studies, 2019)
The notion of a territorial entrepreneurial discovery process has gained much traction through its appearance at the core of smart specialization strategies. This paper uses evidence from eight European regions to explore what in practice is conditioning the emergence of new forms of quadruple-helix governance that underpin this concept. The paper develops a framework that highlights the key factors that have conditioned the governance of RIS3 design and are likely to continue to shape emergent regional entrepreneurial discovery processes.